Differential genotoxic responses to crystalline and amorphous niobium pentoxide nanoparticles in somatic cells of Drosophila melanogaster. - Cardozo, T.R.; Fogliati de Carli, R.; Flores, W.H.; Lehmann, M.; Dihl, R.R. (Toxicology research, 2026)
Niobium pentoxide nanoparticles (NINPs) are increasingly used in technological and biomedical applications due to their chemical stability, biocompatibility, and osteoconductive properties. However, despite their promising use in clinical materials, limited information is available regarding their potential genotoxic effects, particularly in vivo. In this study, we evaluated the genotoxicity of crystalline and amorphous NINPs using the Somatic Mutation and Recombination Test (SMART) in Drosophila melanogaster. Third instar larvae from both standard (ST) and high bioactivation (HB) crosses were exposed to NINPs at concentrations ranging from 0.25 to 4.0 mg/mL. Survival rates were assessed, and mutant spots were scored in adult wings to detect somatic mutation and recombination events. Crystalline NINPs induced a significant increase in the frequency of mutant spots in both ST and HB crosses, indicating genotoxic activity through both mutagenic and recombinagenic mechanisms. In contrast, amorphous NINPs did not show any genotoxic effect under the same conditions. The survival rates remained above 70% for crystalline and above 80% for amorphous NINPs, suggesting that neither form caused systemic toxicity. These results highlight the influence of crystallinity, on nanomaterial biological activity, and reinforce the importance of detailed physicochemical characterization in toxicological assessments.